A Simple Process to Fabricate Micro Flux Sources with High Magnetic Field Gradient - Cuong, Le Viet; Thang, Pham Duc; Hien, Nguyen The (Communications in Physics, 2014)
In this paper, we present a fabrication process to produce the micro-sized magnetic structures based on the hard magnetic powders. Under the magnetic field originated from a micro patterned hard magnetic film, these magnetic powders are magnetically aligned to form arrays of the micro magnets on a polydimethysiloxane (PDMS) substrate. The high magnetic field gradient and stable magnetic flux can be obtained at certain micro-sized area on the surface of the micro magnets. The fabricated structures have been used for trapping iron oxide particles. Generally this fabrication process is simple, low cost and the micro magnets can be used for further applications in biology, medicine and beyond.